Online child sexual exploitation: a new MIS challenge - Demetis, Dionysios S. (2021)
© 2021, Association for Information Systems. All rights reserved. This paper deals with the difficult yet increasingly important MIS phenomenon of online child sexual exploitation (online CSE). Through the use of secondary and publicly available data from the Federal Bureau of Investigation, as well as primary data from a cybercrime police unit in the United Kingdom, this study takes a grounded theory approach and organizes the role that technologies and social actors play in shaping online CSE. The paper contributes to IS theory by providing a consolidated model for online CSE, which we call the technology and imagery dimensions model. This model combines the staging of the phenomenon and the key dimensions that depict how the use of technology and imagery both fuels and defuses the phenomenon. In informing the construction of the model, the paper extracts, organizes, and generalizes the affordances of technology and discusses the role of information systems in detecting online CSE